Infusum Daun Alpukat Sebagai Inhibitor Kristalisasi Kalsium Oksalat pada Ginjal (THE AVOCADO LEAVES INFUSUM AS INHIBITOR ON RENAL CALCIUM OXALATE CRYSTALIZATION) - Madyastuti, Rini; Widodo, Setyo; Wientarsih, Ietje; Harlina, Eva (Jurnal Veteriner; Vol 16 No 4 (2015), 2016)
Urine crystal is a crystal nucleus which tend to form urine stone. The case of urine stone seems to beincreased every year. Crystallization could induce acute tubular necrosis which impact on renal dysfunction.The signs of this condition are high level of urea, creatinine and decrease glomerulus filtration rate. Theobjective of this research was to evaluate the effects of infusum Persea americana Mill as an inhibitorcrystallization which induced by ethylene glycol on white male rats. 20 male rats were divided into 4groups; K1 as negative group received only distilled water ad libitum, K2 as positive group receiveddistilled water containing ethylene glycol, K3 (dose 5%) and K4 (dose 10%) as treatment groups receivedwater containing ethylene glycol and avocado leaves infusion. Phytochemsitry screening of infusion avocadoleaves consisted of flavonoid, saponin, tanine and quinone. Result of analysis showed that the level ofureum and creatinine on K2 was higher than K3 and K4 group. The increased level could be inhibited byinfusion avocado leaves. The measurement of glomerular filtration rate in treatment groups wassignificantly different (p<0.05). Descriptive histopathology observation showed that renal lesio in grouptreatment (K3 and K4) were declined. Large crystal calcium oxalate on K2 group was observed by usingpolarized microscope, whereas small crystal calcium oxalate were seen in the infusion of avocado leavesgroups. These result showed the ability of infusion of avocado leaves as an inhibitor on the growth ofcrystallization calcium oxalate
Keywords: avocado; Persea americana Mill; infusion; crystal; calcium oxalate; ethylene glycol